PEMENUHAN ATAS PERUMAHAN SALAH SATU UPAYA PENANGGULANGAN KEMISKINAN - Diasana Putra, I Dewa Gede Agung; Gde Yana, Anak Agung (Jurnal Natah; Vol. 5, No. 2 Agustus 2007)
The efforts to tackle poor people problems are through basic right fulfilment like food, health, education, work, water, sanitation and housing. Housing is one of fulfilment which difficult to get by poor people in Indonesia. About 4,5 millions backlog unit of housing, also improving of slump area that are the problems of housing in Indonesia. The objective of this study is to know the fulfilment strategy of housing and settlement for poor people, to carrying out of Nation Strategy of tackling poverty especially housing. In Order to achieve this objective, this research uses literature studies method from any reference. Building material engineering is one method to obtain the cheap houses with safety, comfort and health aspect, whether standardization construction system and modular coordination’s system.
Keywords: standardization, modular coordination.